Draft Annual Plan (1993-94) Volume-I Introduction, Sectoral Review and Statements, Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1993)
Against the approved outlay of Rs. 280.00 Crores for the Seventh Plan of this territory, the Planning Commission provided an outlay of Rs. 685.00 Crores Eighth Five Year Plan 1992-97. the allocation for the first year i.e. Annual Plan 92-93 is 155.00 Crores and it is expected that the entire outlay will be utilized. the shortfall is anticipated in the Sector "shipping" owing to non-finalisation of the purchase of the 3rd passenger-cum-cargo vessel from the Polish Firm. However, the Shipping Corporation of India is being pursued to purchase an alternate vessel immediately.
Andaman and Nicobar Administration